EVALUATION OF RICE DISTILLER’S GRAINS WITH SOLUBLES (RDDGS) IN COMMERCIAL BROILER DIET ON HEMATO-BIOCHEMICAL PARAMETERS, AND INTESTINAL HISTOMORPHOLOGY - Srikanth Kaninde; A. Ashok; K. Premavalli; C. Bandeswaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted at Department of Poultry Science, Madras Veterinary College, Chennai to evaluate the effect of inclusion of RDDGS in commercial broiler diet on hematological, serum biochemical parameters. A total of 144 commercial day-old broiler chickens were allotted to four treatments with three replicates and 12 birds per replicate. Experimental diets were prepared by including RDDGS at 0, 5, 10, 15% at the expense of soyabean meal was prepared to be nearly isocaloric and isonitrogenous as per BIS (2007) standards. At the end of the experiment blood was collected from one male and one female from each replicate and analyzed for serum biochemical and hematological parameters. Statistical analysis of data revealed that there was no significant (P>0.05) difference in the hematological, serum biochemical and intestinal histomorphology parameters. It can be concluded that the RDDGS can be included up to 15% in commercial broiler diets without effecting the hematological and serum biochemical parameters.